2020
DOI: 10.1039/c9sc05992j
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and intermolecular interception of a photochemically generated terminal uranium nitride

Abstract: Photolysis of the U(iv) azide LArU(NImDipp) generates a reactive uranium nitride intermediate that can be intercepted by nucleophilic substrates – the first example of intermolecular chemistry of a rare photochemically generated uranium nitride.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…, to stabilize a rare U-Fe bond and separately generate a highly reactive uranium-nitride species. 57,58 Regardless, the ancillary ligand coordination in these systems provides additional bonding contributions and potential ligand strain effects that can compete with or affect the actinide-arene bonding.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…, to stabilize a rare U-Fe bond and separately generate a highly reactive uranium-nitride species. 57,58 Regardless, the ancillary ligand coordination in these systems provides additional bonding contributions and potential ligand strain effects that can compete with or affect the actinide-arene bonding.…”
Section: àmentioning
confidence: 99%
“…49 On this note, the use of tethered ligand manifolds to encourage supported actinide-arene interactions has become a popular approach within recent years. 47,48,[50][51][52][53][54][55][56][57][58][59] Bart, Meyer, and coworkers rst demonstrated that uranium-arene d-bonding was a key feature of their U(III) complex [( t Bu, t BuArO) 3 Mes]U, 50 while Arnold and coworkers showed that redox isomerization of the trans-calix [2]benzene [2]pyrollide (bz 2 pyr 2…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, complexes containing An=N bonds are known to mediate a variety of important and challenging small molecule transformations. [16][17][18] For example, Mazzanti's U(III) nitride [K 3 {U(OSi(O t Bu) 3 ) 3 } 2 (μ-N)] is able to mediate the capture and functionalization of N 2 . 19,20 Likewise, the U(IV) nitride, [Cs{U(OSi(O t Bu) 3 ) 3 } 2 (μ-N)], can activate both H 2 21 and CO. 22 Among these complexes, the terminal U(V) nitride, [U(Tren TIPS )(N)]  (Tren TIPS = N(CH 2 CH 2 NSi i Pr 3 ) 3 ), is especially notable.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, widespread access to terminal actinide nitrides has proven elusive. 18,26 The majority of reported U(V) nitrides feature bridging nitride ligands that are capped by U(IV) ions, [27][28][29][30] which complicates the subsequent electronic structure analysis. 31 These observations point to the need for new synthetic routes to these materials, which would enable synthetic control over oxidation state, symmetry, and capping group identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation